2016
DOI: 10.1007/s10661-016-5406-0
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations, spatial distribution, and risk assessment of soil heavy metals in a Zn-Pb mine district in southern China

Abstract: China is one of the largest producers and consumers of lead and zinc in the world. Lead and zinc mining and smelting can release hazardous heavy metals such as Cd, Pb, Zn, and As into soils, exerting health risks to human by chronic exposure. The concentrations of Cd, Zn, Pb, and As in soil samples collected from a PbZn mining area with exploitation history of 60 years were investigated. Health risks of the heavy metals in soil were evaluated using US Environmental Protection Agency (US EPA) recommended method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 42 publications
3
20
0
Order By: Relevance
“…The Pb-Zn mine in Huize County, Yunnan Province, is an important mineral resource in China, and it has been exploited for 300 years . Several studies have focused on heavy metal pollution and risk assessment in the Huize Pb-Zn mining area (Zou et al 2014;Qi et al 2016). Smelting activities were the main contributors to the high concentrations of Cd and Pb in the topsoil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pb-Zn mine in Huize County, Yunnan Province, is an important mineral resource in China, and it has been exploited for 300 years . Several studies have focused on heavy metal pollution and risk assessment in the Huize Pb-Zn mining area (Zou et al 2014;Qi et al 2016). Smelting activities were the main contributors to the high concentrations of Cd and Pb in the topsoil.…”
Section: Introductionmentioning
confidence: 99%
“…The mobility of Cd in soils was higher than that of Pb. Pb contributed to the highest hazard quotient (57.0-73.9%) in the hazard index (Li et al 2015c;Qi et al 2016). However, the relationship between the soil aggregate composition and the characteristics of Cd and Pb has received less attention.…”
Section: Introductionmentioning
confidence: 99%
“…To be specific, S. J. Lu et al 6 discovered that the high ecological risk of the area was most likely related to acid mine drainage and mining complexes in the soil around the Pb-Zn mine in Huize County, China. J. Y. Qi et al 7 evaluated the health risks of heavy metals in soils collected from a Pb-Zn mining area with exploitation history of 60 years in southern China, and discovered that Cd and Zn were found mainly in the upper 60 cm of the soil, whereas Pb was mainly in the upper 40 cm, and concluded that there was a high health risk, especially for children. S. C. Obiora et al 8 assessed the level of heavy metal contamination of soils caused by PbZn mining activities in Enyiba, southeastern Nigeria, and they revealed that the soil quality had deteriorated around the Pb-Zn mines.…”
Section: Introductionmentioning
confidence: 99%
“…Such plants would then become sources of food poisoning in the ecosystem food web. Human are also capable of being affected by soil heavy metals in three major ways including direct ingestion (this pathway is more common among children), direct inhalation through the mouth or nose, and dermal adsorption of soils adhered to the skin (Qu et al 2012;Qi et al 2016). By using Igeo and EF (Figs.…”
Section: Discussionmentioning
confidence: 99%